Metacognition Ability of Students in the Learning of Control Variable Strategy Assisted with Scientific Teaching Materials - Nurul Lita Azizah, Mutiara; Isnaeni, Wiwi; Imam Supardi, Kasmadi (Universitas Negeri Semarang, 2020)
Strategy Variable Control (CVS) with scientific teaching material is expected to be able to prepare students to face the challenges of the 21st century, especially in mastering metacognition abilities. This study has purpose to analyze the influence of CVS with scientific teaching materials on metacognition abilities of learners. It was done in grade VII SMP PGRI 1 Ajibarang in the first semester of the academic year of 2019/2020. The sampling technique in this study was purposive sampling. The method used in this study was quantitative method with quasy experimental design using control group design. The data in this study was metacognition abilities collected through questionnaires and observation sheets. The data of metacognition ability were analyzed using regression, coefficient of determination, N-Gain Test, and T-Test. The test results and the regression coefficient of determination showed a significance value of 0.000 > 0.05, therefore, CVS with scientific teaching material has significant effect on the ability of metacognition 83.6%. The N-Gain Test Results indicated the level of increase in the ability of metacognition in the experimental group which is higher than the control group. The results of T-test showed a significance value of 0.00 0> 0.05, therefore, there is a difference in the average score of the experimental group and the control group. Based on the results of this study, it can be concluded that CVS with scientific teaching material has a significant effect on the ability of metacognition.